Language education and intercultural style - Hysenaj, Valdet; Mujaj, Hasan (Technium Social Sciences Journal, 2021)
Language education in the state of Kosovo is not given due attention during schooling at all levels of education. A major flaw in education at the country level. Language education is a broad, very broad and highly contemplative notion. It captures a long range of sub-factors of personality formation, so it is not just a matter of language, but also of other components of various social activities. However, the state does not deal with this major identity issue because the statesmen, ministers, deputies, etc. themselves. they do not know how to write no or no, nor to discuss according to the laws of the standard Albanian language. Very big surprise! For any criticism.